Resource use and health outcomes of paediatric extracorporeal membrane oxygenation. Issue 2 (21st February 2005) - Van Litsenburg, R; De Mos, N; Edgell, D; Gruenwald, C; Bohn, D J; Parshuram, C S
Abstract : The use of extracorporeal membrane oxygenation can be rationalised by the assumption that non-zero survival after refractory cardiorespiratory failure represents improved outcome. Survivors may have cognitive and or functional morbidities, require complex ongoing care, and as a consequence consume considerable healthcare resources.